IMPLEMENTASI ATRAKSI WISATA HALAL PASCA-PANDEMI COVID-19 - Jumaidin Jumaidin (Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2022)
Abstrak: Tujuan dari penelitian ini adalah untuk menerapkan kegiatan wisata halal secara berkelanjutan setelah masa pandemi covid 19 dan peningkatan kegiatan ekonomi masyarakat sekitar desa wisata tersebut. Penelitian ini berada di timur kabupaten Lombok Barat letaknya di Kecamatan Kuripan tempatnya di desa Kuripan Selatan. Dalam hal penelitian yang relevan penulis membandingkan dengan jurnal, buku, tesis, dan sebagainya terutama pada hasil penelitian terbaru. Data penelitian diperoleh melalui observasi, dokumentasi dan wawancara. Sampel yang digunakan dalam penelitian adalah beberapa stakeholder dan masyarakat yang terlibat dalam kelompok kegiatan keagamaan dengan sistem dari anggota untuk anggota.Hasil dari penelitian ini diharapkan dapat memberikan informasi bahwa kegiatan wisata keagamaan dapat membantu ekonomi masyarakat khususnya di pulau lombok dan wisatawan baik domestik dan internasional. Data yang diperoleh diolah dengan menggunakan analisis deskriptif kualitatif. Prosedur Penelitian merupakan aktivitas ilmiah yang sistematis terarah dan bertujuan. Prosedur atau langkah yang ditempuh dalam penelitian ini. Tahap pra lapangan, tahap pekerjaan lapangan, tahap analisis data. Analisis pendekatan kualitatif menggunakan analisis data,pengumpulan data, reduksi data dan penarikan/verifikasi kesimpulan. Sehingga hasil penelitian berurutan secara jelas dan seksama. Hasil analisis deskriptif kualitatif menunjukkan bahwa terdapat kegiatan keagamaan yang dilaksanakan oleh masyarakat maupun stakeholder (Pokdarwis) yang terlibat dalam kegiatan keagamaan di desa wisata kuripan selatan. Kata Kunci: atraksi; wisata halal; pasca-pandemi covid-19 Abstract: The purpose of this research is to implement halal tourism activities in a sustainable manner after the COVID-19 pandemic and increase the economic activity of the community around the tourist village. This study is located in the east of West Lombok district, located in Kuripan District, where it is located in the village of South Kuripan. South Kuripan village has a tradition that is a group of religious activities carried out for generations by the community around the southern Kuripan tourist village with a welfare system for members, each group has about twenty-five members.In terms of relevant research, the author compares it with journals, books, theses, theses and so on, especially on the results of the latest research. Understanding halal tourism itself is a tourism that puts forward Islamic Shari'a which has been contained in the Qur'an and As-Sunnah, tourism Halal has a vision that tourism is carried out without violating the values ​​and ethics in Islamic teachings. Thus, halal tourism can be interpreted as tourism that can protect or prevent visitors from committing sins (Adinugraha et al., 2018). The method that the author uses is a method with a qualitative approach.Research data obtained through observation, documentation and interviews. The sample used in this study are several stakeholders and the community who are involved in religious activity groups with a system from member to member. The results of this study are expected to provide information that religious tourism activities can help the community's economy, especially on the island of Lombok and tourists both domestically and internationally. The data obtained were processed using qualitative descriptive analysis. Research procedure is a scientific activity that is systematically directed and purposeful. The procedure or steps taken in this research. Pre-Field Stage, Field Work Stage, Data Analysis Stage. Analysis of the qualitative approach uses data analysis, data collection, data reduction and conclusion drawing/verification. So that the results of sequential research are clear and thorough.The results of the qualitative descriptive analysis indicate that there are religious activities carried out by the community and stakeholders (Pokdarwis) who are involved in religious activities in the southern Kuripan tourist village. In this case, tourism awareness groups need to remind the public to raise awareness of the importance of religious activities carried out, during community involvement and supervision from the Tourism Awareness Group (POKDARWIS) as managers in terms of halal tourism-based religious activities as well as one of the pioneering forms of halal tourism destinations in Indonesia. West Nusa Tenggara. Keywords: attractions; halal tourism; post-covid-19 pandemic